Spontaneous Breathing Test as a Predictor of the Dysfunctional Ventilatory Weaning Response in Intensive Care - Priscila Carvalho de Souza; Ingrid Régia Lopes Jerônimo; Carla de Azevedo Vianna; Andrea Barroso Benevides; Rosimere Ferreira Santana; Marcos Antônio Gomes Brandão (Universidade Federal de Santa Maria, 2020)
Objective: to verify the association of the spontaneous breathing test with the nursing diagnosis of Dysfunctional Ventilatory Weaning Response (00034) and to identify the accuracy measures of the spontaneous breathing test for the nursing diagnosis. Method: a cross-sectional study conducted with 42 patients in critical care. Fischer's exact test verified the association, and the accuracy measures were calculated with Medcalc Software Online®. Results: the association between the test and the diagnosis was significant (p=0.0079). The highlighted accuracy measures were 77.42% specificity (58.90 - 90.41), positive likelihood ratio of 3.22 (1.53 - 6.79), and diagnostic odds ratio of 9.14 (1.90 - 44.01). Conclusion: the study verified the existence of an association between the outcome of the spontaneous breathing test and the Dysfunctional Ventilatory Weaning Response (00034), with statistical significance. It also indicated the adequacy of three accuracy measures for the nursing diagnosis.